Identifying Classroom Management Problems and Their Causative Factors in Creating Effective Classrooms: Identifikasi Masalah Pengelolaan Kelas Dan Faktor Penyebabnya Dalam Mewujudkan Kelas Yang Efektif - Rahma Alfirdaus; Astuti Darmiyanti (At-Tathbīq: Journal of Education and Learning, 2025)
Improving the quality of the education process has always been a highlight for various groups. A quality education process is certainly not carried out carelessly, there needs to be techniques and strategies to produce quality education. This article presents how class management problems make classes ineffective, which are taken from several reading books and articles. Therefore, this article can be used as one of the study materials for prospective professional teachers who are deepening their knowledge in the tertiary environment in the field of education, more specifically teacher education. Because the role of a professional teacher is certainly a big demand and challenge in order to create a pleasant learning experience and can provide the best impression for students.